Genetic diversity and evolution of SARS-CoV-2 - Phan, Tung (Infection, genetics and evolution, 2020)
COVID-19 is a viral respiratory illness caused by a new coronavirus called SARS-CoV-2. The World Health Organization declared the SARS-CoV-2 outbreak a global public health emergency. We performed genetic analyses of eighty-six complete or near-complete genomes of SARS-CoV-2 and revealed many mutations and deletions on coding and non-coding regions. These observations provided evidence of the genetic diversity and rapid evolution of this novel coronavirus. •A novel coronavirus is officially known as SARS-CoV-2.•Eighty-six complete or near-complete genomes of SARS-CoV-2 were analyzed.•Many mutations and deletions on coding and non-coding regions of SARS-CoV-2 were found.